Potential use of NOACs in developing countries: Pros and cons - Bista, D.; Stafford, Leanne; Bereznicki, L.; Peterson, G. (Springer, 2014)
Purpose: Although vitamin K antagonists (VKAs) are effective for long-term thromboprophylaxis in atrial fibrillation (AF), their limitations have led to widespread underutilisation, especially in the developing world. Novel oral anticoagulants (NOACs) have emerged as promising alternatives to VKAs, although there are some particular considerations and challenges to their introduction in developing countries. This review summarises the current state of antithrombotic management of AF in the developing world, explores the early evidence for the NOACs and describes some of the special considerations that must be taken into account when considering the role of the NOACs within developing countries' health care systems. Methods: A literature search was conducted via PubMed and Google Scholar to find articles published in English between the years 2000 to 2014. Search terms used were "atrial fibrillation", "oral anticoagulants", "warfarin", "NOACs", "dabigatran", "rivaroxaban", "apixaban", "edoxaban", "time in therapeutic range", "International Normalized Ratio" "cost- effectiveness", "stroke", "adverse-drug reactions" and "drug-drug interactions", together with the individual names of developing countries as listed by the World Bank. We reviewed the results of randomized clinical trials, relevant retrospective and prospective studies, case-studies and review articles. Results: Many developing countries lack or have sporadic data on the quality of AF management, making it difficult to anticipate the potential impact of NOACs in these settings. The utilisation of anticoagulants for AF appears highly variable in developing countries. Given the issues associated with VKA therapy in many developing countries, NOACs offer some potential advantages; however, there is insufficient evidence to advocate the widespread replacement of warfarin at present. VKAs may continue to have a role in selected patients or countries, especially if alternative monitoring strategies can be utilised. Conclusion: The evaluation of the introduction of NOACs should consider safety, budget concerns and the quality of oral anticoagulation care achieved by each country. Prospective registries will be important in developing countries to better elucidate the comparative safety, efficacy and cost-effectiveness of NOACs and VKAs as NOACs are introduced into practice. © 2014 Springer-Verlag.